الضريبة على ارباح الشركات - إيمان, حميدتوا (unuversity of eloued- جامعة الوادي, 2023)
في حالة ما إذا كانت الأنشطة الممارسة من طرف شركات أعضاء التجمع خاضعة لمعدلات مختلفة للضريبة على أرباح الشركات، يخضع الربح المتأتي من هذا التجميع للضريبة لمعدل 19% في حالة ما إذا كان رقم الأعمال تابعا لهذا المعدل المتفوق. و في الحالة العكسية، يسمح بتوحيد الأرباح تبعا لصنف رقم الأعمال (19%و 25%) (المادة 3 من ق. In the event that the activities carried out by the companies of the members of the association are subject to different tax rates on corporate profits, the profit derived from this association is subject to tax at the rate of 19% in the event that the turnover is subject to this superior rate. In the opposite case, it is allowed to consolidate profits according to the category of turnover (19% and 25%) (Article 3 of Q.
Keywords: الضريبة ، الشركات